PENGARUH AKUNTANSI SOSIAL TERHADAP PENGUKURAN KINERJA PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN MANUFAKUR DI JAWA TENGAH DAN DAERAH ISTIMEWA YOGYAKARTA) - Laila, Nur Laila (Jurnal Analisis Bisnis Ekonomi, 2010)
Social Accounting according to Belkaoui (2007), born from opinion that accounting as human being instrument in the life must be in accordance with social purpose too. Work measuring company needful for determine success to achieve purpose company for maximise wealth from stakeholders. Social accounting consist of some factor that is govermental regulation, community pressure, environmental organization pressure and amssmedia pressure. This research purpose to analysis influence social accounting to work measuring company. Object of this research is manufacture company in Central Java and Special Region of Yogyakarta. Hyphothesis test to do with multiple regression analysis. Result of this research referred that govermental regulation influential negative to work measuring company with probability 0,011 < 0,05 and price t hitung is negative, community pressure do not influence to work organization pressure do not influence to work measuring company with probability 0,446 p value > 0,05 and massmedia pressure do not influence to work measuring company with probability 0,050 p value = 0,050 and price of t hitung is negative.